2007
DOI: 10.1007/s10620-007-9802-8
|View full text |Cite
|
Sign up to set email alerts
|

The ICE Inhibitor Pralnacasan Prevents DSS-Induced Colitis in C57BL/6 Mice and Suppresses IP-10 mRNA but Not TNF-α mRNA Expression

Abstract: Previously we demonstrated an ameliorating effect of the interleukin-1beta converting enzyme (ICE) inhibitor pralnacasan on dextran sulfate sodium (DSS)-induced colitis. This study investigates the effects of pralnacasan on cytokine expression in DSS-induced colitis. Colitis was induced by oral administration of DSS. Mice were treated intraperitoneally with the ICE inhibitor pralnacasan (50 mg/kg body weight twice daily). Body weight as well as the presence of occult blood or diarrhea was monitored daily. Subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 40 publications
(35 reference statements)
5
53
0
1
Order By: Relevance
“…Similar results have been observed in caspase-1-deficient mice or by administration of soluble IL-1Ra antibody, which both led to profound amelioration of DSS-induced colitis (21). In addition, our group has shown that pralnacasan, a small molecule caspase-1 inhibitor, significantly reduced severity of DSS colitis (19,22). Other groups have reported that Casp1 -/-mice have aggravated colonic inflammation (23).…”
Section: Introductionsupporting
confidence: 85%
“…Similar results have been observed in caspase-1-deficient mice or by administration of soluble IL-1Ra antibody, which both led to profound amelioration of DSS-induced colitis (21). In addition, our group has shown that pralnacasan, a small molecule caspase-1 inhibitor, significantly reduced severity of DSS colitis (19,22). Other groups have reported that Casp1 -/-mice have aggravated colonic inflammation (23).…”
Section: Introductionsupporting
confidence: 85%
“…Siegmund et al [23] reported protection of caspase-1 -/-mice from the deleterious effects of DSS administration and our group found that treatment of mice with the caspase-1 inhibitor pralnacasan ameliorated colonic inflammation [24,25] . In contrast, a recent study showed that caspase-1 -/-mice have aggravated colonic inflammation [7] .…”
Section: Role Of the Nlrp3 Inflammasome In Ibdmentioning
confidence: 63%
“…Indeed, inhibition of caspase-1 by the specific inhibitor pralnacasan [26] attenuated DSS-induced colitis, this effect being mediated by suppression of proinflamatory IL-18 and IFN-g.…”
Section: Discussionmentioning
confidence: 99%